Risk Factors for Nutritional Rickets in Children of Northern Kerala - Soumya Jose; Bindu and P M Kutty (IOSR Journal of Dental and Medical Sciences, 2015)
Objective: To assess the risk factors causing nutritional rickets among children in our part of world. Subjects And Methods: 47 children with rickets and 47 control children matched for age and sex were recruited over a 18 month period in a tertiary care hospital in northern kerala.Diagnosis was based on clinical, radiological, biochemical parameters and response to treatment. Children who presented in our OPD with non nutritional illness were used as control. A specially designed questionnaire was administered by one of the investigators to both mothers of patients and control subjects to assess the role of social, nutritional and other related factors in the pathogenesis of nutritional rickets. Results :There was no significant difference between cases and controls for prematuriy,birth weight, birth order, breast feeding and weaning practices.68% rickets patients did not have significant sun exposure but this was not statistically significant(ρ value 0.69).None of the children in study and control group received vitamin D supplementation according to current guidelines. The study group had significantly higher percentage of first degree relatives with rickets than controls (21% v/s 4%; ρ value 0.01). Conclusion: Nutritional rickets is multifactorial condition.We presume that most important predisposing factor for nutritional rickets in our area is gestational vitamin D deficiency.